Problem-based Learning and Student Critical Thinking to Improve Learning Achievement at Private Universities in Aceh - Ibrahim Ibrahim; Nurul Akmal; Marwan Marwan (STAI Hubbulwathan Duri, 2021)
This study aimed to determine the effectiveness of problem-based teaching and learning models to increase learning achievement and the relationship with students' critical thinking skills. This study used an experimental method with a design pretest-posttest control group. The population in this study were all semester four students of the Biology Education Department. Analysis of experimental data to measure the achievement of student learning outcomes with t-test and critical thinking skills using percentage description analysis, using statistical computer software programs. The research results show an increase in learning achievement, with an average N-gain for problem-based learning units is 70.9 (moderate) and 57.93 (moderate) for conventional classes. The t-test results show that the t-count value is 3.61 and the t-table is 1.991, so t-count t-table. The conclusion is that there are differences in learning outcomes in implementing problem-based teaching and learning models to increase learning outcomes with critical thinking skills of four at the Private University of Aceh Province, Indonesia.